Hindu women in religious orders: Understanding their well-being in old age. Issue 3 (2nd July 2016) - Pandya, Samta P.
ABSTRACT: The study aims to understand determinants of well-being of Hindu women in old age who have committed their lives to religious orders. Data was obtained across eight countries from a sample of 12, 082 older Hindu women renunciants belonging to two religions orders: Brahmakumaris and Chinmaya Mission. An e-mail questionnaire was administered comprising basic background profile questions and four scales to measure aspects of well-being, satisfaction with life, and happiness. The analysis of variance, logistic regression, and structural equation models showed that religiosity, spirituality, work done in the order, and length of association positively influenced well-being, life satisfaction, and happiness. Internal covariances among the independent variables had further compounding effects. Religiosity and spirituality serve to be protector variables for older Hindu women renunciants, influencing their well-being, life satisfaction, and happiness. Study of older women in religious orders and working with them must form a part of aging studies and practice.